2016
DOI: 10.1093/tropej/fmw049
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anemia and its Risk Factors among Children under 36 Months Old in China

Abstract: This study aims to evaluate the prevalence and sociodemographic factors of anemia in children <36 months old in China. In this study, data of 24 235 children were investigated from 32 primary health care (PHC) facilities in 11 province-level regions. Pearson χ-test and logistic regression model were used to estimate potential risk factors associated with anemia. The overall prevalence of anemia was 24.4%, and 32.8% children from rural areas were anemic, but no statistically significant difference was observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
16
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 22 publications
8
16
0
5
Order By: Relevance
“…Consistent with previous estimates [10,28,29], this study also highlights the constantly and alarmingly high risk of anemia among children under 3 years old in rural China. The results show that about two-thirds of children aged 6-17 months and one-third of the children aged 18-35 months were anemic, and no significant reduction of risk of anemia was found among these children from 2013 to 2016.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous estimates [10,28,29], this study also highlights the constantly and alarmingly high risk of anemia among children under 3 years old in rural China. The results show that about two-thirds of children aged 6-17 months and one-third of the children aged 18-35 months were anemic, and no significant reduction of risk of anemia was found among these children from 2013 to 2016.…”
Section: Discussionsupporting
confidence: 92%
“…And this study recommends that parents (the primary caregivers) should be well informed about their child's nutritional health and the importance of vaccinating their children against all the basic doses of full immunization. Additionally, special care should be taken to closely monitor those households where parents are not well educated, do not have any employment or source of income and young parents who are not experienced in parenting and child care 46,47 .…”
Section: Resultsmentioning
confidence: 99%
“…Though proper dietary consumption and regular intake of iron can substantially reduce the burden of anaemia 43,45 , still a majority of the children under age five years are anaemic in India. Thus, it could be mentioned that educated mother/parents do take care of dietary intake and are more aware of their child's nutritional health than those parents having no formal education 36,39,46 . Studies conducted in different country settings like-Asia, Africa, Latin America, and the Middle East show positive association between parental education and child's nutritional status 47 and in this study also a parental education gradient in stunting and anaemia is observed which indicates lower burden of child stunting and anaemia among the children of higher educated parents.…”
Section: Discussionmentioning
confidence: 99%
“…Iron deficiency is a common cause of anemia in children and is associated with 86-93% of anemia in children [4]. Many observational studies indicate that the independent risk factors of anemia in children include preterm birth, low birth weight, and maternal anemia [5][6][7][8][9]. Moreover, childhood anemia is closely related with feeding practice, complementary food introduction, social demographic characteristics, and family income [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%